VD_FINDINFO AI 184/12 - 68/2015 vom 11. März 2015 - VD Tribunal cantonal (2015)
LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE | 17 al. 1 LAI, 29 al. 1 LAI, 4 al. 1 LAI, 8 al. 1 LPGA, 88a al. 1 RAI